E-Leaflet-Based HIV/AIDS Education and Adolescent Knowledge - Hamalding, Hermawati; Makmur, Fadilla; Sumiati, Sumiati; Batubara, Khairunnisa (Chakra Brahmanda Lentera Institute, 2025)
Background: HIV/AIDS continues to be a threat to public health worldwide, including in Indonesia, particularly among the elderly population, who are particularly vulnerable to the risks associated with inadequate knowledge and information access. Purpose: This study aims to understand the impact of e-leaflet media on Adolescent understanding about HIV/AIDS Methods: The study's design uses a quantitative approach with a quasi-experimental methodology and a single-group pretest-posttest design. With a one-group pretest-posttest design and inclusion criteria that included being between the ages of 15 and 18, registered as active students, eager to participate, and able to read and comprehend Indonesian, 62 teenagers in all were chosen at random to join in the quasi-experiment. Students who did not finish the questionnaire or were enrolled in other HIV/AIDS education programs were excluded. A knowledge questionnaire regarding HIV/AIDS with 15 multiple-choice and true/false items served as the tool. Three experts used Aiken's V to examine the content validity of this questionnaire, which was adapted and adjusted from Ministry of Health recommendations and prior research material. Results: The results showed that the instrument was valid, with results >0.85. The Kuder-Richardson 20 (KR-20) method was used for reliability testing, and the results showed a high dependability rating of 0.78. Three steps were used to obtain the data: the pretest, the intervention (digital e-leaflets), and the posttest five days later. The Wilcoxon Signed Rank Test data analysis revealed a significant difference (p <0.001), suggesting that e-leaflet media education was successful in raising adolescents' awareness of HIV/AIDS prevention. Kurnia Jaya Persada University's Health Research Ethics Committee has approved this study, and prior to participation, each subject gave their informed consent. Conclusion: Based on these results, e-leaflets are a useful educational tool that should be incorporated into adolescent health promotion initiatives in order to stop the early spread of HIV/AIDS